Skogsbilvägens tillgänglighet och framkomlighet - Svederberg, William; Olsson, Rikard (2022)
A well-functioning system of forest roads is important for enhancing accessibility to the forest and lowering costs for acquiring raw material. The construction of forest roads has been an important aspect of forestry since the mechanization in the second half of the 20th century and the procedure of constructing roads has varied over time. In 1983 the Swedish Forest Agency released their handbook “Principles of calculus for forest road planning1” which aimed to be a tool for anyone working with economical calculations in forest road projects.